J. Donald Gillaspey letter to Michael C. Newlon regarding birds seen during fall 1984 - Gillaspey, J. Donaldet al (1984)
J. Donald Gillaspey letter to Michael C. Newlon was regarding birds seen during fall 1984. He and three other observers saw five bird species near Lamoni, including an immature Pine Grosbeak. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed/flatbed